The Influence of Social Studies Teacher Learning Process Service Quality on the Satisfaction of Class VIII Students at SMPN 2 Sei Bamban - Marinus Gomgom Samosir; Rusydi Ananda; Nuriza Dora (Yayasan Zia Salsabila, 2024)
This study is to investigate how class VIII students' satisfaction at SMPN 2 Sei Bamban is impacted by the caliber of social studies teacher learning process services. Ex post facto techniques are used in this quantitative research design. With 62 responders/students, class VIII pupils made up the study's population. In this study, documentation studies, questionnaires, and observation were the methods employed to acquire data. Research employing partial t-tests yielded results demonstrating that student satisfaction is influenced by the quality of social studies teacher learning process services, with a t-count value of 3.385 and a t-table value of 1.999. This indicates that the t-count value is greater than the t-table (3.385 > 1.999), indicating that the research decision is acceptable. Additionally, the R Square table displays 0.160, or 16.0%, based on the coefficient of determination test findings.